Design, characterization and control of MR damper for two-wheeler applications. (2022) - Devikiran, Pinjala; Shravya, Pendyala; Puneet, N.P.; Kumar, Hemantha
Abstract: The research on Automotive systems is always an ongoing process with varied advancements in different sectors. One such sector is suspension system and the recent trends in vehicular suspension has taken a turn towards semiactive suspension considering its salient features like cost effectiveness and low power consumption with variable damping force. This research work presents the design of radial flux Magneto Rheological damper (MRD) with magnetic field analyzed using the FEMM tool. The designed MR damper has fabricated and characterized for modelling the damper in order to simulate the quarter car model of two wheeler rear suspension. The entire simulation was carried out using MATLAB/SIMULINK.